The effect of weld residual stresses and their re-distribution with crack growth during fatigue under constant amplitude loading - Liljedahl, C. David M.; Zanellato, Oliver; Fitzpatrick, Michael E.; Lin, J.; Edwards, Lyndon (Elsevier, 2010)
In this work the evolution of the residual stresses in a MIG-welded 2024-T3 aluminium alloy M(T) specimen during in situ fatigue crack growth at constant load amplitude has been measured with neutron diffraction. The plastic relaxation and plasticity-induced residual stresses associated with the fatigue loading were found to be small compared with the stresses arising due to elastic re-distribution of the initial residual stress field. The elastic re-distribution was modelled with a finite element simulation and a good correlation between the experimentally-determined and the modelled stresses was found. A significant mean stress effect on the fatigue crack growth rate was seen and this was also accurately predicted using the measured initial residual stresses.
Keywords: Neutron diffraction; Residual stresses; Fatigue; Welding; Finite element analysis